Evaluation of the pre-service Turkish teachers’ attitudes towards reading habit according to some variables - Murat ÖZBAY; Hasan BAĞCI; Yusuf UYAR (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
Turkish teachers’ attitudes towards reading habit have an important influence on their students in acquiring reading habit. Thus, the variables affecting the in-service and preservice Turkish teachers’ attitudes towards reading must be investigated. The purpose of this study is to determine if pre-service Turkish teachers’ attitudes towards reading habit show difference depending on various variables. The data were gathered from, 1st, 2nd, 3rd, and 4th graders studying at the Department of Turkish Education in Gazi Education Faculty at Gazi University. Likert type attitude scale was used for gathering data in this research. Independent-Samples T-test, Scheffe Test, One Way ANOVA are used for analyzing the data. The findings of the research assert that pre-service Turkish teachers’ attitudes towards reading habit are influenced by gender, reading frequency, and whether they read periodicals. In this study it is proposed that students at all grades of education must be given activities which have positive influence on attitudes towards reading habits. And, also, the school libraries and public libraries must be arranged to support positive attitudes through reading habits.